Paying for Pediatric Home Health Care: How Families of Children With Medical Complexity Navigate Gaps in Coverage. Issue 3 (July 2021) - Raisanen, Jessica C.; Ruth, Alexandra; Donohue, Pamela K.; Detwiler, Kathryn; Fratantoni, Karen; Huff, Susan M.; Boss, Renee D.
Abstract : Limited private and public financing of home health care for children with medical complexity can have harmful and costly consequences. Little is known of how parents and professionals in the United States navigate coverage for these services or how payer restrictions are shaping service quality. Qualitative interviews were conducted with families and professionals (eg, prescribers, providers, administrators of pediatric home health care [PHHC]) caring for children with medical complexity. Interview transcripts were analyzed using inductive thematic analysis. In total, 47 families and 45 professionals from across 31 states and the District of Columbia had experiences with the full range of PHHC services. Participants detailed the need to patch together multiple insurances and payment programs to cover a child's home health needs. They described nontransparent eligibility determinations that do not reflect the diagnostic uncertainty and static functional status that is common for many children. Coverage denials are common, leaving gaps in care that can potentiate downstream cost escalation. Evidence-based health care reform must ensure that children get the PHHC needed to maintain function and reduce the need for hospital-based services. Recommendations are offered to improve PHHC financing and care for the most medically vulnerable children and their families. Abstract : Supplemental Digital Content is Available in the Text.